A PRÁTICA DA CITAÇÃO NA UNIVERSIDADE AS REFERÊNCIAS À INFORMAÇÃO CIENTÍFICA EM TRABALHOS ACADÊMICOS. - dos Santos, Cosme Batista (Trabalhos em Lingüística Aplicada)
Studies on quotation as object of academic or university literacy are still rare in the field of applied linguistics in Brazil. However, quotation practices are a privileged object of study to help us understand the complexity of access to theoretical references and to research writing at university levels. This work adopts as central assumptions information literacy in its inclusive approach (SILVA, 2008) and ecological literacy in its sociodiscursive approach (BARTON, 1998; IVANIC, 1998; KLEIMAN, 1995). Based on such assumptions, the literacy event mediated by research writing and by the use of quotation in university environments should be seen as a discursive practice (COMPAGNON, 1996; BOCH & GROSSMANN, 2001 and 2002). From this perspective, the research on modes of referencing, including source quotation, allows to shed light into problems regarding access to information and to theoretical discourse, as well as access to university literacy in different countries and sociocultural contexts. This work analyzed thirty (30) academic end-of-course papers from two Brazilian universities - the State University of Bahia (UNEB) and the State University of Campinas (Unicamp) - and from one Portuguese university - the University of Porto (UP). Out of the total papers analyzed, we identified six hundred ninety-nine (699) references to theoretical discourse, including quotations; of that total, 249 belonged to UNEB students, 195 to Unicamp students and 255 to UP students. After the quantitative analysis we noticed that - just as observed by French researchers Françoise Boch and Francis Grossmann- students from both countries tend to use more often autonomous quotations, that is, the literal insertion of parts of theoretical discourse references, rather than reformulations and evocations. Data suggest that such trend appears to be linked to the fact that students are at initial stages of research writing practices and not to sociocultural context or nationality related factors.